Grid tied PV System using modular multilevel inverter - N., Sujitha; Subudhi, Partha Sarathi; S., Krithiga; S., Angalaeswari; T., Deepa; D., Subbulekshmi (Institute of Advanced Engineering and Science, 2019)
A grid tied photovoltaic system using modular multilevel inverter topology is proposed in this paper. Basic unit structure of modular multilevel inverter used in this system is capable of converting DC power from PV array to AC power for feeding power to the household loads or utility grid. The proposed modular multilevel inverter structure has lesser power electronic devices compared to the existing multilevel inverter topologies. The proposed system generates a nearly sinusoidal signal and achieves better output profile with low total harmonic distortion. Simulation of the proposed system is carried out in MATLAB/Simulink software and the results are presented.